2008
DOI: 10.1259/dmfr/55898096
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variety of the soft palate in normal individuals: a digital cephalometric study

X Li2,
et al.

Abstract: Introduction: Soft palate is a fibromuscular portion constituting the back of roof of the mouth which is essential for phonation, deglutition, respiration and velopharyngeal competence. Objective: To study various morphologies of soft palate, difference in proportion of each type and their differencesamong gender and agegroups in Nepalese sample. Materials & Method: Aretrospective study was conducted on patients seeking orthodontic treatment. 263 lateral cephalograms were classified on the basis of radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 12 publications
11
59
1
1
Order By: Relevance
“…Whereas Sshaped soft palate was not observed in the study group. Type 1 soft palate is the most common variety of soft palate seen in population [You et al, 2008]. These findings are in consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whereas Sshaped soft palate was not observed in the study group. Type 1 soft palate is the most common variety of soft palate seen in population [You et al, 2008]. These findings are in consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Similar study was carried out in normal individuals by You et al (2008). To our knowledge this is the first study to evaluate the morphological changes of soft palate in oral submucous fibrosis using digital lateral cephalogram.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The variation of the soft palate morphology may be a new explanation for surgical failure and the soft palate may need to be repaired in various patterns. 3 Dentist and radiologist who observes the finding of hooked/ butt appearance of soft palate on lateral cephalogram should suspect the strong possibility of the presence of OSAS. …”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 3,4 Pepin et al found the "hooked" appearance of the soft palate in awake patients, which indicated a high risk for obstructive sleep apnoea syndrome (OSAS). In general, most OSA patients seem to have a high body mass index (BMI) shows severe apnoea problems.…”
Section: Introductionmentioning
confidence: 99%